Does copper treatment of commonly touched surfaces reduce healthcare-acquired infections? A systematic review and meta-analysis. Issue 4 (December 2020) - Albarqouni, L.; Byambasuren, O.; Clark, J.; Scott, A.M.; Looke, D.; Glasziou, P.
Summary: Background: Healthcare-acquired infections (HAIs) cause substantial morbidity and mortality. Copper appears to have strong antimicrobial properties under laboratory conditions. Aim: To examine the potential effect of copper treatment of commonly touched surfaces in healthcare facilities. Methods: Controlled trials comparing the effect of copper-treated surfaces (furniture or bed linens) in hospital rooms compared with standard rooms on HAIs were included in this systematic review. Two reviewers independently screened retrieved articles, extracted data, and assessed the risk of bias of included studies. The primary outcome was the occurrence of HAIs. Findings: In total, 638 records were screened, and seven studies comprising 12, 362 patients were included. All included studies were judged to be at high risk of bias in two or more of the seven domains. All seven studies reported the effect of various copper-treated surfaces on HAIs. Overall, this review found low-quality evidence of potential clinical importance that copper-treated hard surfaces and/or bed linens and clothes reduced HAIs by 27% (risk ratio 0.73, 95% confidence interval 0.57–0.94; I 2  = 44%, P =0.01). Conclusion: Given the clinical and economic costs of HAIs, the potentially protective effect of copper treatment appears to be important. The current evidence is insufficient to make a strong positive recommendation. However, it would appear worthwhile and urgent to conduct larger publicly funded clinical trials into the impact of copper treatment.